2015
DOI: 10.4172/2375-4427.1000135
|View full text |Cite
|
Sign up to set email alerts
|

Intelligibility of Speech Produced by Children with Hearing Loss: Conventional Amplification versus Nonlinear Frequency Compression in Hearing Aids

Abstract: Objective: This study aimed to 1) investigate the influence of nonlinear frequency compression (NLFC) in hearing aids on intelligibility of speech produced by children with hearing loss; and 2) examine whether clinicians' or parents' judgments might be correlated with those of inexperienced listeners.Methods: Twenty-seven adult listeners with normal hearing who reported no experience listening to speech produced by people with hearing loss were asked to judge the intelligibility of speech samples of eight hear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 36 publications
0
1
0
Order By: Relevance
“…So far, there has been a number of studies examining the efficacy of NLFC on various aspects of speech perception including phoneme and word recognition, sentence perception, and sound-quality perception (Glista et al, 2009;Wolfe et al, 2010Wolfe et al, , 2011Wolfe et al, , 2017Ching et al, 2013;Parsa et al, 2013;Brennan et al, 2014Brennan et al, , 2017Hopkins et al, 2014;McCreery et al, 2014;Picou et al, 2015;Alexander and Rallapalli, 2017;Chen et al, 2020;Xu et al, 2020). While many studies reported lower detection thresholds and improved perceptual accuracies with NLFC-fitted hearing aids in comparison to hearing devices fitted with conventional processing (CP) (Ching et al, 2013;Alexander et al, 2014;Ching and Rattanasone, 2015), some studies reported no additional benefit in phoneme audibility, or sentence recognition with the NLFC algorithm (Perreau et al, 2013;Bentler et al, 2014;Picou et al, 2015). In addition, within those studies that found improved perceptual performance with NLFC, some reported that the benefit of NLFC was not ubiquitously shown in all tested subjects (Simpson et al, 2005;Glista et al, 2009;McCreery et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…So far, there has been a number of studies examining the efficacy of NLFC on various aspects of speech perception including phoneme and word recognition, sentence perception, and sound-quality perception (Glista et al, 2009;Wolfe et al, 2010Wolfe et al, , 2011Wolfe et al, , 2017Ching et al, 2013;Parsa et al, 2013;Brennan et al, 2014Brennan et al, , 2017Hopkins et al, 2014;McCreery et al, 2014;Picou et al, 2015;Alexander and Rallapalli, 2017;Chen et al, 2020;Xu et al, 2020). While many studies reported lower detection thresholds and improved perceptual accuracies with NLFC-fitted hearing aids in comparison to hearing devices fitted with conventional processing (CP) (Ching et al, 2013;Alexander et al, 2014;Ching and Rattanasone, 2015), some studies reported no additional benefit in phoneme audibility, or sentence recognition with the NLFC algorithm (Perreau et al, 2013;Bentler et al, 2014;Picou et al, 2015). In addition, within those studies that found improved perceptual performance with NLFC, some reported that the benefit of NLFC was not ubiquitously shown in all tested subjects (Simpson et al, 2005;Glista et al, 2009;McCreery et al, 2014).…”
Section: Introductionmentioning
confidence: 99%